The effect of dissolved nickel and copper on the adult coral Acropora muricata and its microbiome. (July 2019) - Gissi, Francesca; Reichelt-Brushett, Amanda J.; Chariton, Anthony A.; Stauber, Jenny L.; Greenfield, Paul; Humphrey, Craig; Salmon, Matt; Stephenson, Sarah A.; Cresswell, Tom; Jolley, Dianne F.
Abstract: The potential impacts of mining activities on tropical coastal ecosystems are poorly understood. In particular, limited information is available on the effects of metals on scleractinian corals which are foundation species that form vital structural habitats supporting other biota. This study investigated the effects of dissolved nickel and copper on the coral Acropora muricata and its associated microbiota. Corals collected from the Great Barrier Reef were exposed to dissolved nickel (45, 90, 470, 900 and 9050 μg Ni/L) or copper (4, 11, 32 and 65 μg Cu/L) in flow through chambers at the National Sea Simulator, Townsville, Qld, Australia. After a 96-h exposure DNA metabarcoding (16S rDNA and 18S rDNA) was undertaken on all samples to detect changes in the structure of the coral microbiome. The controls remained healthy throughout the study period. After 36 h, bleaching was only observed in corals exposed to 32 and 65 μg Cu/L and very high nickel concentrations (9050 μg Ni/L). At 96 h, significant discolouration of corals was only observed in 470 and 900 μg Ni/L treatments, the highest concentrations tested. While high concentrations of nickel caused bleaching, no changes in the composition of their microbiome communities were observed. In contrast, exposure to copper not only resulted in bleaching, but altered the composition of both the eukaryote and bacterial communities of the coral's microbiomes. Our findings showed that these effects were only evident at relatively high concentrations of nickel and copper, reflecting concentrations observed only in extremely polluted environments. Elevated metal concentrations have the capacity to alter the microbiomes which are inherently linked to coral health. Graphical abstract: Image 1 Highlights: There is an increase in mining activities in tropical regions. Corals may be exposed to metal contaminants. There is limited data for the effects of metals on adult corals and their microbiome. We exposed the coral Acropora muricata to Cu and Ni separately. High concentrations of Cu and Ni caused bleaching and changes in the microbiome community of A. muricata . Abstract : Bleaching and changes in the coral microbiome community structure were only observed in corals exposed to high concentrations of dissolved nickel and copper.